"Remote learning - pluses and minuses" - Sattarov Inayat Saparbayevich; Sattorova Khadicha Inayat qizi (Zien Journals, 2023)
A few decades ago, anybody who wanted to learn something new had to make frequent visits to libraries or educational institutions. You only need a computer with internet connectivity today in order to learn. The key benefits and drawbacks of distant learning will be discussed in this article.
Keywords: technology; Internet connections; online instruction